Effect of platelet-rich fibrin in reducing postoperative complications after impacted third molar surgery: a prospective, randomized controlled clinical trial - Alparslan Esen; Dilek Menziletoğlu; Bozkurt Kubilay Işık (Gazi University, 2017)
Objective: The first aim of this study was to evaluate the effect of platelet-rich fibrin (PRF) on pain, swelling, and trismus after mandibular impacted third molar surgery without the use of postoperative antibiotics. A second aim was to evaluate the patients' quality of life (QOL) during the postoperative period. Materials and Method: Forty patients, who had bony impacted, mesio-angular mandibular third molars that were fully covered with mucosa, were selected. Patients were divided into two groups: PRF was placed in the socket in the first group and, traditional surgery was performed in the second group (the socket was left empty). The same surgeon performed all surgeries under local anesthesia. No antibiotics were prescribed after surgery. The outcome variables were pain, swelling, trismus, and QOL over a follow-up period of seven days. Results: The mean age of the patients was 23.3 (±3.9) years in the first group, and 23.3 (±4.6) years in the second group. Statistical analyses of the postoperative results showed that there were no significant differences between the groups with regard to pain, swelling, trismus, and QOL scores (p>0.05). Conclusion: The present study showed that PRF use had no significant effect on the postoperative pain, swelling, trismus, and QOL after impacted third molar surgery.